Trust and power as predictors of tax compliance: Global evidence - Mas’ud, Abdulsalam; Abd Manaf, Nor Aziah; Saad, Natrah (Center of Sociological Research, 2019)
Slippery Slope Framework has attracted exceptional attention from researchers in economic psychology and taxation field through validation by renowned scholars via variety of surveys and experimental designs. However, application of cross-sectional analysis in validating the framework has been scant, the available studies being focused on a single continent only. This study aims to test the assumptions of “Slippery Slope Framework” through examination of the influence of trust in authorities and power of authorities on tax compliance globally. The sample of 158 countries was selected as of 2016. Data was analyzed through Ordinary Least Squares Regression Analysis. The results reveal that trust in authorities significantly influences tax compliance, but power of authorities does not. Additionally, the interaction effect of trust and power on tax compliance has not been established through this cross-country analysis. Practically, the results suggest that authorities should ensure judicious use of taxpayer monies in the provision of public goods and services, and also fairness and equity among taxpayers. Eventually, these will enhance trust and improve tax compliance. Theoretically, the study calls for disaggregation analyses where each continent will be studied individually for replication of these findings and establishing the interaction effect wherever possible.